Rijkuo-Maja and Silbo-Gåmmoe - towards the question of female shamanism in the Saami area - Bo Lundmark (Scripta Instituti Donneriani Aboensis, 1987)
Among the Saamis shamanism has been predominantly male, at least from what we know of it through 17th and 18th century accounts. However, among the forest Saamis of Arvidsjaur the traditions about Rijkuo-Maja are still alive. The general belief was that she was master of the noaidie's arts. Judging by tradition, the thunder god, Horagalles or Atjakatj, seems to have been the object of her particular devotion. In the recorded traditions about Rijkuo-Maja, there are a number of things which conflict with the woman's role in the cult as represented in the older sources. According to these, the sacrificial sites were "as a rule a forbidden area for women". We find the next female figure of interest to our discussion among the mountain Saamis of Täma. She was called Anna Greta Matsdotter and came from Vapsten, being better known by the name of Silbo-gåmmoe or Gammel-Silba. According to the tradition, she was using the drum. There is no information on whether they were elected or rewarded as shamanistic functionaries. Neither Rijkuo-Maja or Silbo-gåmmoe functioned on the orders of a Saami community or sijte, but they represent a stage where it was possible for a woman to perform in new roles which were previously taboo to them. From another point of view, they are possibly latter-day exponents of an even earlier, extant shamanism with female characteristics in the Saami.